Fundamentals of data engineering : plan and build robust data systems / Joe Reis and Matt Housley. - Reis, Joe (Joseph); Housley, Matthew L., 1977- (O'Reilly, 2022)
Data engineering has grown rapidly in the past decade, leaving many software engineers, data scientists, and analysts looking for a comprehensive view of this practice. With this practical book, you'll learn how to plan and build systems to serve the needs of your organization and customers by evaluating the best technologies available through the framework of the data engineering lifecycle. Authors Joe Reis and Matt Housley walk you through the data engineering lifecycle and show you how to stitch together a variety of cloud technologies to serve the needs of downstream data consumers.